Psychotropic Drugs Levels in Seminal Fluid: A New Therapeutic Drug Monitoring Analysis? - Mazzilli, Rossella; Curto, Martina; De Bernardini, Donatella; Olana, Soraya; Capi, Matilde; Salerno, Gerardo; Cipolla, Fabiola; Zamponi, Virginia; Santi, Daniele; Mazzilli, Fernando; Simmaco, Maurizio; Lionetto, Luana (Frontiers in Endocrinology, 2021)
Abstract: The aim of this observational study was to develop a new quantitative liquid chromatography-mass spectrometry (LC-MS/MS) method for Therapeutic-Drug-Monitoring (TDM) of psychotropic drugs in seminal fluid to investigate potential gonadotoxic effects in patients with reduced fertility. After the validation of the LC-MS/MS method for psychotropics levels determination in seminal fluid, we included 20 male partners of infertile couples with idiopathic and/or unexplained male infertility, treated with psychotropic medications for more than 3 months and 10 untreated fertile controls. General and andrological clinical examination; semen analysis and seminal drugs and metabolites levels determination were performed for each subject. Of the 20 patients included, 6 were treated with antidepressants; 4 with benzodiazepines and 10 with antipsychotics. Seminal drugs and metabolites levels were detectable in all samples. In particular, alprazolam, olanzapine and levetiracetam showed seminal and serum similar concentrations, while fluoxetine, quetiapine and aripiprazole were detectable, but seminal levels were significantly lower than the serum therapeutic range. Sperm progressive motility was significantly reduced in subjects treated with psychotropic drugs compared to the untreated controls (p=0.03). Sperm concentration and progressive motility were significantly reduced in subjects treated with antipsychotics compared to the untreated controls and to the other classes of psychotropics (p<0.05). In conclusion, this study reports a validated LC-MS/MS method for the detection of seminal psychotropic levels and preliminary data suggesting a potential correlation of seminal psychotropics with alterations of sperm concentration and motility. Pending larger studies, semen TDM might represent a new pivotal tool in the clinical management of reduced fertility in males treated with psychotropic medications.